2003
DOI: 10.1046/j.1471-4159.2003.01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Caspr/paranodin with tumour suppressor schwannomin/merlin and β1 integrin in the central nervous system

Abstract: Caspr/paranodin is an essential neuronal component of paranodal axoglial junctions, associated with contactin/F3. Its short intracellular domain contains a conserved motif (GNP motif) capable of binding protein 4.1 domains [FERM domains (four point one, ezrin, radixin, moesin)]. Schwannomin/merlin is a tumour suppressor expressed in many cell types, including in neurons, the function and partners of which are still poorly characterized. We show that the FERM domain of schwannomin binds to the paranodin GNP mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 68 publications
(177 reference statements)
1
20
0
Order By: Relevance
“…In our initial screen of proteins that might anchor merlin to lipid rafts, we found that three putative merlin-binding proteins, CD44 (12,48), ␤ 1 integrin (49,50), and paxillin (51), were not required for merlin to be in lipid rafts. In fact, these three proteins were found to be Triton soluble in Optiprep gradients under the same conditions in which merlin was raft associated (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In our initial screen of proteins that might anchor merlin to lipid rafts, we found that three putative merlin-binding proteins, CD44 (12,48), ␤ 1 integrin (49,50), and paxillin (51), were not required for merlin to be in lipid rafts. In fact, these three proteins were found to be Triton soluble in Optiprep gradients under the same conditions in which merlin was raft associated (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit antibodies against paranodin (L51), Caspr2, and syndecan 4 have been described previously (Menegoz et al, 1997;Denisenko-Nehrbass et al, 2003;Goutebroze et al, 2003). The antineurofascin antibody reacting with NF155 and NF186 was generated by immunizing rabbits with the common intracellular region of the protein (residues 1065-1175; GenBank accession number AY061639) fused to glutathione S-transferase.…”
Section: Methodsmentioning
confidence: 99%
“…Schwannomin-like immunoreactivity has been reported in paranodal regions and SchmidtLanterman incisures (SLIs) (Scherer and Gutmann, 1996), which are cytoplasmic channels interrupting the compact myelin. In neurons, schwannomin can associate with the cytoplasmic tail of the paranodal protein paranodin/Caspr (Denisenko-Nehrbass et al, 2003), whereas in Schwann cells, it is localized to the plasma membrane through a paxillin-mediated interaction with ␤1-integrin (Obremski et al, 1998;Fernandez-Valle et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, N-terminal merlin can be associated with Caspr/paranodin, an axonal transmembrane glycoprotein enriched at paranodal junctions and important for the reciprocal axo-glial signaling [80]. Merlin also interacts with βII-spectrin - another molecule supporting the axonal cytoskeleton at paranodes (see Table 1) - essential for myelinated axon domain organization [30,49,81].…”
Section: The Hereditary Disease Neurofibromatosis Typementioning
confidence: 99%
“…In contrast to merlin isoform 2, which is specifically implicated in axon structure maintenance, both major merlin isoforms appear to have equal potency in affecting Nrg1 type III.
Figure 2 Interaction of neuronally expressed merlin with axonal proteins essential for axon-Schwann cell signaling. Merlin in neurons has been shown to interact with two axonal proteins in the paranode region of myelinated axons: Caspr/paranodin [80] and βII-spectrin [30]. Furthermore, merlin regulates the expression of Nrg1 type III [85], an axon surface molecule with growth factor-like impact on Schwann cell behavior.
…”
Section: The Hereditary Disease Neurofibromatosis Typementioning
confidence: 99%